An experimental study on of the effect of various deflectors used for light trucks in Indian subcontinent. (February 2019) - Chowdhury, Harun; Juwono, Raymond; Zaid, Mohamed; Islam, Rezaul; Loganathan, Bavin; Alam, Firoz
Abstract: Aerodynamics plays an important role on the external shape of the vehicle and any other additional structures such as deflector attached to it. It has been noted that significant numbers of light truck are manufactured and operated in the Indian subcontinent without any aerodynamic aspect. Therefore, the main objective of this study is to analyze the aerodynamic impact of several deflectors or fairings used in light trucks available in Bangladesh and Pakistan. The study was performed by computer modelling, rapid manufacturing of physical models, wind tunnel testing including computational fluid dynamics (CFD) analysis. Drag forces generated by each model were analyzed and compared. The results show that the deflectors used in most Bangladeshi and Pakistani trucks manufactured locally are not aerodynamically efficient as they can increase the overall aerodynamic drag by up to 22%. By replacing these deflectors with an aerodynamic shaped fairing can reduce the fuel consumption by 12%.